Road kills of non‐human primates: a global view using a different type of data. (13th June 2019) - Hetman, Mateusz; Kubicka, Anna Maria; Sparks, Tim H.; Tryjanowski, Piotr
Abstract: Road infrastructures and collisions with vehicles negatively affect many animal populations globally. However, data on road kills of non‐human primates are very limited, not only due to the rare character of this phenomenon, but also due to the geographical bias of reporting in scientific references. As an alternative, we used data from social media (YouTube videos, online articles and blogs) in addition to searching the existing scientific information. The reports in scientific papers were published in 1994–2018, and the reports in social media dated from 2010 to 2018. In total we collated information on 46 non‐human primate species and 368 individual animals that were killed due to collisions with vehicles on four continents. Numbers of observations and numbers of species in each continent were as follows: Africa, 46 and 15; Asia, 247 and 14; South America, 72 and 16; and Europe, 3 and 1. Only two of the species found in our social media internet search belonged to the International Union for Conservation of Nature's Endangered category, but a higher‐than‐expected number of fatalities was in the Vulnerable category. In scientific papers, seven Endangered species were reported as victims of collisions. Often it was young individuals crossing roads that were killed by vehicles. Primates are very charismatic species, so collisions are likely to be reported on social media. We believe that the information we have collected can make a valid contribution to the debate on wildlife‐vehicle collisions, and can be used to plan ways to avoid or mitigate road kills of non‐human primates.